Perancangan Aplikasi “Empatiku” Berbasis Android Untuk Peningkatan Aksesibilitas Informasi Bagi Penyandang Disabilitas - Rahman, Rakhmadi; I, Ikbal; V, Viandra; Azzahra, Maryam (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
In an increasingly advanced digital era, technology has a very important role in increasing information accessibility for all individuals, including people with disabilities. One approach that has proven effective in improving their quality of life is the development of Android-based applications specifically designed to meet their needs. This article discusses the design of the